PIC16F84A and PIC16F873 parallel programmer [microfilm] - Ahmad Yazid Abu Zarim (Skudai : Universiti Teknologi Malaysia, 2002)
Project Paper (Bachelor of Electrical Engineering (Electronics)) - Universiti Teknologi Malaysia, 2003